A Multisite Quality Improvement Project to Standardize the Assessment of Pressure Ulcer Healing in Veterans with Spinal Cord Injuries/Disorders. (June 2016) - Thomason, Susan S.; Powell-Cope, Gail; Peterson, Matthew J.; Guihan, Marylou; Wallen, Erik S.; Olney, Christine M.; Bates-Jensen, Barbara
ABSTRACT: OBJECTIVE: The objective was to implement the evidence-based Spinal Cord Impairment Pressure Ulcer Monitoring Tool (SCI-PUMT) in 23 Spinal Cord Injury/Disorders Centers (SCI/D) in the Veterans Health Administration (VHA). SETTING: A collaborative was held in Minnesota that was attended by key personnel from SCI/D Centers in the VHA. METHODS: This initiative was based on a 3-year longitudinal study that established the validity and reliability of a novel pressure ulcer monitoring tool for persons with spinal cord impairment. A multifaceted evidence-based strategy was used to implement the Institute for Healthcare Improvement's framework of Plan-Do-Study-Act. The plan was executed by clinical champions who implemented the tool in their respective SCI/D Centers following a conference that used both didactic and practicum approaches. OUTCOMES: A 15-item toolkit was developed to educate clinicians and patients regarding use of the SCI-PUMT. Toolkit elements were frequently accessed over the VA intranet (n = 3254). The 1.5-day national conference rolled out the new tool to the SCI/D Centers. Pre/post SCI-PUMT knowledge of the SCI-PUMT improved by 78% during the conference. Following the conference, periodic conference calls cemented the implementation efforts of the SCI-PUMT clinical champions and barriers were mitigated.